Implementasi Tugas dan Wewenang Panwaslu Kecamatan Di Kabupaten Pekalongan Di Masa Pandemi Covid-19 - Naili Karimah; Abdul Hamid (Department of Constitutional Law, Faculty of Sharia, Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
In the 2020 simultaneous elections during the COVID-19 pandemic, this will certainly have an impact on weakening supervision so that in anticipating the risks that will arise, optimal monitoring is needed. The formulation of the problem in this research is; 1) How is the implementation of Law Number 6 of 2020 in the implementation of the duties and authorities carried out by the Sub-district Panwaslu in Pekalongan Regency in the 2020 Pilkada? 2) what are the obstacles for the Pekalongan Sub-district Panwaslu in carrying out their duties and functions. This type of research is library research, using an empirical legal study approach. The results of the study concluded that the implementation of the duties and authorities of the Sub-district Panwaslu as the election supervisor had carried out supervision from the implementation of supervision, the stages of holding elections, then submitting the findings of alleged violations, to the follow-up process for any alleged violations. Obstacles experienced but the Sub-district Panwaslu in Pekalongan Regency carried out its duties and authorities in accordance with applicable regulations.